Construction of a recombinant baculovirus encoding Japanese encephalitis virus envelope protein - Nhiên, Nguyễn Thanh Thùy; Kamei, Kaeko; Mori, Hajime; Thước, Trần Linh (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 29-38, 2005